2004
DOI: 10.1016/j.virol.2004.06.043
|View full text |Cite
|
Sign up to set email alerts
|

Acute hepatotoxicity of oncolytic adenoviruses in mouse models is associated with expression of wild-type E1a and induction of TNF-α

Abstract: Replication competent adenoviruses with various E1 modifications designed to restrict their replication to tumor cells are being evaluated as oncolytic agents in clinical trials. In mouse models, we observed that such oncolytic adenoviruses showed greater hepatotoxicity than E1-deleted adenovirus vectors following intravenous administration. Additional studies in congenic BALB/c, nude, and beige/Scid mice demonstrated dose-dependent hepatotoxicity and indicated that beige/Scid was the most sensitive strain. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 60 publications
0
35
1
Order By: Relevance
“…Even replication-defective Ad or Ad virus components induced toxic responses in the host. Acute induction of proinflammatory cytokines such as IL-6, IL-1β and TNF-α and elevated serum transaminases are common findings following Ad therapy [7,11,12,16,22,37,48]. These responses are presumably due to interactions of Ad or its components with macrophages and liver Kupffer cells [49].…”
Section: Discussionmentioning
confidence: 99%
“…Even replication-defective Ad or Ad virus components induced toxic responses in the host. Acute induction of proinflammatory cytokines such as IL-6, IL-1β and TNF-α and elevated serum transaminases are common findings following Ad therapy [7,11,12,16,22,37,48]. These responses are presumably due to interactions of Ad or its components with macrophages and liver Kupffer cells [49].…”
Section: Discussionmentioning
confidence: 99%
“…34 Despite this inability to release E2F, hepatic toxicity is observed when this virus is injected systemically, as E1A transcription is not regulated and takes place in normal cells. 18 For the systemic treatment of disseminated cancer, E1A transcription control is required. In this regard, the E2F-1 promoter has previously been used to direct E1A transcription in response to Rb pathway deregulation.…”
Section: Discussionmentioning
confidence: 99%
“…18 Strong immunostaining was detected throughout livers from AdwtRGD-treated mice. In contrast, even at the highest dose of ICOVIR-7 (1 Â 10 11 viral particles per mouse), little E1A was detected, indicating that the E2F-responsive promoter effectively restricts the expression of E1A in liver (Figure 3a).…”
Section: Icovir-7 Replication Is Restricted In Normal Cellsmentioning
confidence: 95%
See 1 more Smart Citation
“…It has previously been shown that TNF-␣ is likely to be involved in host responses to Ad vectors in vitro and in vivo (34). Recently, Shayakhmetov et al (35) have reported that IL-1 signaling, not TNF-␣ signaling, is involved in Ad vector-associated liver toxicity after i.v.…”
Section: Elimination Of Il-6 Signaling Reduces Liver Toxicitymentioning
confidence: 99%